Moisture Content Throughout the Pelleting Process and Subsequent Effects on Pellet Quality - H. K. Wecker; R. N. Kort; C. J. Fiehler; A. M. Ogles; J. R. Froetschner; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
This experiment was designed to evaluate the effects of steam addition to the conditioner on moisture content throughout the pelleting process and subsequent effects on pellet quality. Treatments consisted of diets pelleted with no steam and steam added to achieve conditioning temperatures of 145 and 190°F. Conditioner retention time was set at 30 s and diets were pelleted with a ¼ × 2 ½ inch pellet die. Pellet samples were collected and immediately placed in an experimental counterflow cooler for 15 min. All treatments were replicated at 3 separate time points to provide 3 replicates per treatment. Mash, conditioned mash, hot pellets, and cooled pellet samples were collected for moisture content analysis, and cooled pellets for pellet durability index (PDI). Data were analyzed with pelleting run as the experimental unit and time period as the blocking factor. Moisture samples were analyzed as a 3 × 4 factorial of steam-conditioning and sample location. There was a steam-conditioning × sample interaction (P<0.01) for moisture. Moisture in mash samples was similar for all treatments. For the no steam treatment, there was no difference in moisture content between the mash, conditioned mash, and hot pellets; however, moisture decreased in cooled pellets. For the 145°F treatment, there was an increase in moisture from mash to conditioned mash, followed by a decrease in both hot pellets and cooled pellets. For the 190°F treatment, moisture increased from mash to conditioned mash, and decreased in hot pellets and cooled pellets. Increasing conditioning temperature from no steam to 190°F increased (P<0.01) PDI from 3.3, 59.1, to 91.1%, respectively. In conclusion, increasing feed temperature from 97.2 to 190°F via steam addition increased the conditioned mash moisture content by 4.2%, resulting in improved pellet quality.
Keywords: pelleting; moisture content; pellet quality; steam conditioning